Aqua Mater: On the Meaning of the Theonym Betatun - Ledo Caballero, Antonio Carlos (Gerión. Revista de Historia Antigua, 2021)
The finding of an inscription containing the Iberian theonym Betatun in the surrounding area of the Late Iberian sanctuary in Las Atalayuelas site (Fuerte del Rey – Torredelcampo, Jaén) opens up new perspectives for the study of Iberian religion. In this paper we try to demonstrate that in the name of the divinity is implicit a common element that would relate it to several toponyms and hydronyms, both ancient and modern, and this is water.
Keywords: Iberian Gods; Iberian Shrines; Syncretisms; Toponymy; Hydronymy